Small Medium Micro Business Strategies During Covid-19 Time In Barru District, Barru Regency (Sharia Financial Management Analysis) - Sultan, Sudarmi; H, M Nasri; Damirah (Institut Agama Islam Negeri Parepare, 2022)
The Covid-19 pandemic that occurred in Indonesia caused health attacks but also attacked the economic side. MSMEs as the Micro, Small and Medium Enterprises sectors are experiencing the impact caused by the Covid-19 pandemic. Many MSMEs are affected by this pandemic, especially those in Barru District. So this research aims to see the extent of the economic impact, especially for MSMEs in Barru District. Given that MSMEs are a source of income for the community. The type of research used is field research that uses a qualitative approach generated from written words and behaviours that can be observed through observation, interviews, and documentation. Data reduction, data presentation, and conclusion drawing are the data analysis techniques used. The results of this study indicate that MSMEs during the COVID-19 period greatly impacted the incomes of MSMEs from Barru's perspective. Many SMEs have had to stop their business due to various problems caused by the Covid-19 pandemic. Various strategies are carried out using Islamic financial management strategies, namely planning to keep the business running, implementation in planning is by previous plans, and evaluation is to measure the extent to which the Islamic frame has achieved performance.